Assessment of anxiety symptoms among intensive care nursing personnel in Greece - Karanikola, Maria; Stathopoulou, Hariklia; Kalafati, Maria; Terzi, Angela-Beth; Mpouzika, Meropi; Papathanassoglou, Elizabeth (My University, 2009)
Factors associated with the burnout syndrome and stress symptoms in nurses have been studied worldwide. There has been little study, however to investigate anxiety symptoms in the nursing staff of Greek Intensive Care Units (ICUs). Aim: The purpose of this study was to investigate the intensity of anxiety symptoms and their association with demographic, vocational and educational factors among Hellenic nursing personnel working in ICUs. Method: A descriptive correlational design was applied. The study sample consisted of 229 randomly selected members of the nursing staff employed in public and private adult General Hospitals in Greece. The intensity of anxiety symptoms was measured using Hamilton's scale for anxiety state assessment. Results: The response rate was 78.6%. The overall intensity of anxiety symptoms was found to be mild, with 19.9% of the participants experiencing moderate disturbance and 3.9% experiencing serious disturbance. The most frequent symptoms of anxiety were sleep disturbances, anxious mood, cognitive disturbances and restlessness. In addition, moderate to severe musculoskeletal symptoms were reported by 50% of the participants. Female nurses (MW-U, p =0.006) and nursing staff employed in the public sector (MW-U, p=0.01) presented the most intense symptoms of anxiety. Statistically significant correlation was observed between work experience in the ICU and overall intensity of anxiety symptoms (tau=0.043, p=0.004) and between the number of ICU beds and anxious mood (tau=0.186, p<0.0001). Conclusions: Nursing staff in Greek ICUs experience mild symptoms of anxiety, although one alarming finding was the intensity of symptoms such as anxious mood, sleep disturbances, restlessness, musculoskeletal problems and cognitive disturbances. The occurrence of these disturbances appears to be related to the ICU staffing patterns.
Keywords: Anxiety; Intensive care unit; Nursing personnel